Determinação por espectroscopia mössbauer dos sítios de ferro em matérias primas geopoliméricas - Alves, Luis Carlos Praxedes (2011)
In this work, geopolymeric precursor materials were studied by Mössbauer spectroscopy. To motivate the work, results of Mössbauer spectroscopy on lateritic soil and concretion and geopolymers produced from them are presented. To study the structure of iron in kaolinites and metakaolinites, geopolymeric most important precursor materials, natural red kaolins with naturally occurring structural iron and white kaolinite doped through iron incorporation reactions in alkaline environments. The Mössbauer spectra of samples of red kaolin showed a doublet of paramagnetic octahedral Fe$^{3+}$ and an amorphous phase. In the calcination process the emergence of hematite due to burning of non-structural iron along with the amorphous phase is observed. In addition, it is also observed the appearance of a second doublet consistent with paramagnetic octahedral Fe$^{3+}$ characteristic of severely deformed metakaolinite. White kaolinite doped with iron showed only a doublet with quadrupole splitting slightly above those obtained in the red kaolin before burning. Burning resulted in the transformation of a fraction of kaolinite in metakaolinite with consequent distortion of the octahedral sites. It is also observed the appearance of hematite due to the existence of iron not incorporated into the clay structure. The spectra of samples milled in stainless steel jars showed a reduction in quadrupole splitting suggesting an accommodation of ions Fe$^{3+}$ octahedra in the kaolinite structure, and the appearance of a second doublet with quadrupole splitting associated with a milling induced larger deformation of the octahedral iron. The spectrum of the sample ground in carbon steel jar showed contamination by metallic iron, which was not seen in the sample ground in the stainless steel jar. In addition to contamination, milling also induced the formation of a fraction of octahedral Fe$^{2+}$. Calcination of this sample transformed metallic iron into hematite and oxidized the Fe$^{2+}$ back to Fe$^{3+} $. Calcination of all ground samples induced the appearance of hematite and the increase of the quadrupole splitting of doublets as a result of kaolinite distortions. These results showed that it is possible to dope kaolinite with iron and to obtain metakaolinite with structural iron through mechanical milling and calcination. With its advantages and disadvantages, both clays are suitable for use as geopolymers precursor materials.